The Role of Price Promotion and Product Quality in Influencing the Intention to Repurchase Cok-Kis Cookies - Vashti, Hannah; Antonio, Tony (KnE Social Sciences, 2021)
Repurchase intention is crucial to the continuity of businesses especially snack businesses. Customer satisfaction is one of the dominant variables influencing repurchase intention. This purpose of this study was to determine the role of price promotion and product quality in affecting customer satisfaction, which in turn influences the repurchase intention of snack products. The sample consisted of 117 people (a minimum sample of 91 was calculated using the Yamane and Isaac and Michael formulas). A questionnaire was given to the participants and data were analyzed quantitatively using SmartPLS version 3.0 (Partial Least Square). The results showed that customer satisfaction had a significant influence on the repurchase interest of Cok-Kis customers. Price promotion and product quality had a significant effect on Cok-Kis customer satisfaction. Customer satisfaction could mediate the effect of price promotion and product quality on the repurchase interest of Cok-Kis customers. Keywords: price promotion, product quality, customer satisfaction, repurchase intention